Death Devil - Sharpe, Jon (Sharpe, Jon. Renegade rifles., 2012)
As a deadly fever rages in the Ozark Mountains, Dr. Belinda Jackson races against time to find a cure with the help of the Trailsman who keeps the outlaws, snake oil salesmen and distrustful denizens at bay.